Interação de nematoides entomopatogênicos com o parasitoide Diachasmimorpha longicaudata (Hymenoptera: Braconidae) para o controle de Ceratitis capitata (Diptera: Tephritidae) - Souza, Mariana Macedo de (2020)
Ceratitis capitata (Diptera: Tephritidae) is considered one of the main pests of fruit production worldwide, due to the damage caused by the larvae which consume the pulp of the fruits, making them unsuitable for commercialization. Currently, Integrated Pest Management has been widely used due to environmental concerns and human health, using a sum of strategies to control fruit flies. Biological control has been the most used since releases of the parasitoid Diachasmimorpha longicaudata (Hymenoptera: Braconidae). However, in some cases, just using the parasitoid is not enough, and it is necessary to adopt another biocontrol agent. In this context, entomopathogenic nematodes (EPN) are promising in the control of C. capitata, as it has a phase in its life cycle in the soil. The association between biological agents can increase the effectiveness of pest control, but it can also produce antagonistic interaction. Thus, the objective of this work was to evaluate the compatibility of EPN with the parasitoid D. longicaudata in the associated control of C. capitata, under laboratory conditions. The bioassays were conducted at the Laboratory of Pathology and Microbial Control of Insects at the Federal University of Lavras - UFLA, under controlled conditions (25 ± 2 ° C, UR 70 ± 10%, 12h photophase). To evaluate the pathogenicity of EPN on larvae of C. capitata parasitized and not parasitized by D. longicaudata, 1mL of suspension containing 100 juvenile infective (IJ)/insect from native and exotic EPN isolates were applied. The effect of the concentrations and the time of infection of the isolate Heterorhabditis sp. Alho in parasitized and non-parasitized larvae. Finally, the behavior of EPN in distinguishing the types of larvae in an arenas with a chance of choice was evaluated. It was found that all EPN were virulent to parasitized and non-parasitized larvae, with the isolate Heterorhabditis sp. Alho the one that caused the lowest mortality of parasitized larvae (79.6%). Larval mortality was proportional to the increase in the concentration of juvenile infectors, requiring a lower concentration of juveniles to cause a high mortality of parasitized larvae, since the LC50 and LC90 of parasitized larvae was only 19.88 and 93.54 IJ/larva, respectively, while the non-parasitized larvae were 45.20 and 181.86 IJ/ larva, respectively. In the choice test, the EPN favored parasitized larvae, causing a mortality of 91.67%. Nematode infection occurs within 12 hours and after this period, there is no increase in mortality regardless of the type of larvae. Thus, it is concluded that parasitized larvae are more susceptible to EPN than non-parasitized larvae, with an antagonistic interaction between the parasitoid D. longicaudata and the EPN, and it is necessary to establish release strategies when the two agents are used for control C. capitata.